The complete mitochondrial genome of Boccardiella hamata (Annelida: Polychaeta: Spionida) - Geon Hyeok Lee; Ha-Eun Lee; Gi-Sik Min (Mitochondrial DNA. Part B. Resources, 2021)
In this study, the complete mitogenome sequence of Korean Boccardiella hamata was determined. This is the first complete mitogenome in the order Spionida. The complete mitogenome of B. hamata is 17,561 bp in length with 12 protein-coding genes (atp8 gene absent), 23 transfer RNAs, 2 ribosomal RNAs, and 1 control region. Interestingly, the gene arrangement of the 12 PCGs of B. hamata is unique, which is very different from that of the other polychaetes currently known. The phylogenetic tree supported the traditional taxonomic position of Spionidae within subclass Sedentaria.